Developing tools as plug‐ins: TOPI 2011 special issue editorial. (18th March 2013) - Bishop, Judith; Notkin, David; Bishop, Judith; Notkin, David
SUMMARY Our knowledge of how to solve software engineering problems is increasingly being encapsulated in tools. These tools are at their strongest when they operate in a pre‐existing integrated development environment (IDE). This approach allows integration with existing elements such as compilers, debuggers, profilers, visualizers, and numerous other development and, often, runtime tools. Tools and environments to increase software quality and productivity have always been an important aspect of software engineering. A plug‐in is a modern way for incrementally adding new tools into existing environments. However, building tools as plug‐ins can be challenging. How do they interact with the core environment? How do they interact with one another ‐ especially since each developer may choose a different set of plug‐ins? How can we share tools across different, and future, core development environments?